Lessons learned from interdisciplinary US national science foundation research traineeship-supported graduate programs - Jyothi Kumar; Michelle R. Worosz; Shin-Han Shiu; Pamela H. Templer; Karen S. McNeal (PLoS ONE, 2026)
The National Science Foundation’s (NSF) Research Traineeship (NRT) Program fosters interdisciplinarity. It is designed to train scholars with the agility to move beyond their strict disciplinary boundaries. The goal of the Program is to create innovative graduate educational opportunities for broad workforce development. We assessed the professional development skills and activities documented in the annual reports of 20 NRT projects to assess which technical and transferable skills were commonly highlighted, how these skills were integrated into their educational programming, which stakeholders were targeted, and how much time was allocated to the associated activities. We found communication (43%), job readiness (42%), and team science (26%) to be the most common professional development skills provided by the 20 NRT projects. We go into greater depth about three of these NRT projects to more deeply characterize programmatic challenges and successes. Then, we highlight strategies to manage potential points of friction and to recommend approaches that could be adopted as part of other graduate professional development projects. These innovations have the potential to promote transformative change in graduate STEAM education, nationwide.